RETRACTED: The struggles and triumphs of Indian women entrepreneurs on their path to achieving work-life harmony and career fulfillment - Kaushik Madhu Bala; Rajharia Poonam (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 456, 00002 (2023), https://doi.org/10.1051/e3sconf/202345600002